Network analysis of the relationship between self-management, self-efficacy, and quality of life among diabetes mellitus patients - Le, Minh H.; Dao, Tran NP.; Le, Ngoc D.; Tran, Van D. (Narra Sains Indonesia, 2025)
Diabetes mellitus (DM) requires constant self-management and self-efficiency, which affects the quality of life among patients. It is important to understand the complex interplay between these factors to improve the results of treatment. The aim of this study was to explore the relationship between self-management, self-efficacy, and quality of life among diabetes mellitus patients. A cross-sectional study of 363 diabetes patients from three public hospitals in Cao Lanh City, Vietnam, was conducted. Self-management, self-efficacy, and quality of life were assessed using the 35-item Diabetes Self-Management Instrument (DSMI), the 6-item Self-Efficacy for Managing Chronic Disease Scale (SECD6), and the 5-item European Quality of Life 5 Dimensions 5 Level Version (EQ-5D-5L), respectively. Network analysis was performed to visually describe the relationship between self-management (which includes five domains of self-integration, self-regulation, interaction with health professionals and other significant people, self-monitoring, and medication adherence), self-efficacy, and quality of life. The network analysis showed that self-monitoring had the highest centrality. Two subscales of self-management, adherence and self-integration, were directly and positively correlated with quality of life, while the interaction was directly and negatively correlated with quality of life. Self-efficacy was positively correlated with self-regulation and self-monitoring, while it was negatively correlated with adherence. A direct positive correlation was also found between self-efficacy and quality of life. In conclusion, these findings highlight the pivotal role of self-management and self-efficacy in enhancing quality of life. Future studies should focus on patient education interventions to enhance adherence and self-efficacy, ultimately improving the quality of life in people with diabetes.